2005
DOI: 10.1016/j.virol.2005.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of HIV-1 entry by (s4dU)35

Abstract: We have previously reported the potent in vitro HIV-1 anti-reverse transcriptase activity of a 35-mer of 4-thio-deoxyuridylate [(s(4)dU)(35)]. In efforts to define its activity in a more physiological system, studies were carried out to determine the stage of viral infection that this compound mediates its anti-viral effect. Results of the studies reported herein show that (s(4)dU)(35) is nontoxic and is capable of inhibiting both single and multi-drug resistant HIV strains (IC(50): 0.8-25.4 microg/ml) in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The C15‐mer binds to a discrete region within thrombin exosite 1 (fibrinogen recognition exosite), which overlaps the platelet receptor and thrombomodulin binding sites [8,16,17]. In our earlier studies, 4‐thio‐deoxyuridylate‐containing oligonucleotides showed high‐affinity binding to certain proteins [18,19]. Here, we examined the effects of 4‐thio‐deoxyuridylate‐containing analogs of the thrombin‐binding aptamer on different hemostatic/thrombotic activities of thrombin and compared them with the effect of C15‐mer.…”
Section: Introductionmentioning
confidence: 99%
“…The C15‐mer binds to a discrete region within thrombin exosite 1 (fibrinogen recognition exosite), which overlaps the platelet receptor and thrombomodulin binding sites [8,16,17]. In our earlier studies, 4‐thio‐deoxyuridylate‐containing oligonucleotides showed high‐affinity binding to certain proteins [18,19]. Here, we examined the effects of 4‐thio‐deoxyuridylate‐containing analogs of the thrombin‐binding aptamer on different hemostatic/thrombotic activities of thrombin and compared them with the effect of C15‐mer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conformational changes in cell surface receptors, coreceptors of HIV and viral envelope proteins, redox changes in these proteins are also required for successful HIV-1 entry and infection. Several inhibitors of protein disulfide isomerase (PDI) as well as cell-surface-thiol interacting agents including thioredoxin, influence HIV infection [14,15] indicating that redox processes active in viral entry could be potential targets for treatment of HIV infection, as we and others reported earlier [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 80%
“…It must be noted that UD29 is a mononucleotide, however, its deoxyoligonucleotide derivatives are also active biologically inhibiting the HIV entry and the telomerase enzyme [18,29,30]. Preliminary results on the activity of some other derivatives of the thiolated nucleotide and polynucleotide have also been reported [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time of addition experiments suggest a target consistent with an early lifecycle event, such as fusion, and this was confirmed using cell-cell fusion experiments. Subsequent investigation led to the determination that (s 4 dU) 35 inhibits viral attachment and is a potent fusion inhibitor with IC 50 of 0.002 µg/ml [29]. Studies indicate that (s 4 dU) 35 binds to CD4 and co-localizes with thioredoxin.…”
Section: Targeting Charge-charge Interactionsmentioning
confidence: 99%